EPIDEMIOLOGICAL CHARACTERISTICS OF PARENTERAL VIRAL HEPATITIS AMONG REINDEER HERDERS IN SOUTH YAKUTIA - A. V. Zotova; S. S. Sleptsova; M. I. Mihajlov; E. Yu. Malinnikova; P. G. Petrova; N. V. Borisova; S. V. Markova; M. E. Ignat’eva; M. N. Andreev (Журнал инфектологии, 2018)
Researches of parenteral viral hepatitis prevalence in Republic of Sakha (Yakutia) showed high frequency of hepatitis B and C infection markers. High level of HBsAg carriage among indigenous nationalities representatives living in isolated ethnic group had been revealed (12,9%). HBsAg and anti-HBc detection frequencies is 12,9% and 76,0% respectively in comparison with 5,8% and 14,6% among newcomer population (p<0,001). In spreading of HBV-infection leading role belong to natural ways which prevalence in majority of age groups. This fact causes necessity of prevention measures correction. Among newcomer population, we can note high level of HCV infection. Results of parenteral viral hepatitis epidemiological distinguishes evaluation among indigenous nationalities in Southern Yakutia shows to necessity of medical care system improvement and special medical programs. To reason that measures we have to perform complex screening researches to parenteral viral hepatitis infection markers.